1985
DOI: 10.1017/s0141347300012040
|View full text |Cite
|
Sign up to set email alerts
|

“Setting Events” as Determinants of Staff Behaviour: An Exploratory Study

Abstract: One of the major problems facing behaviour therapy has been the relative lack of success in bringing about lasting change in complex environments. The difficulty in assessing and understanding these failures may well be due to an unnecessarily narrow view of change in terms of small units of behaviour and short time-scales. In contrast, if one takes a “setting events” perspective, this might generate more explanatory hypotheses by focusing on larger behavioural units and longer time-scales. This exploratory st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Therapeutic approaches that are behavioral in orientation have been demonstrated to be cost effective for schizophrenics and other severely disturbed psychiatric populations, in both inpatient (Paul and Lentz, 1977) and outpatient (Liberman, et al, 1987) settings. Paul and Lentz (1977), for example, concluded that a behavioral token economy is the treatment of choice for chronic psychiatric inpatients when compared to active 'milieu' treatment programs or the medication/custodial care routine commonly provided to these patients.Despite demonstrations of the utility and cost effectiveness of behavioral programming in psychiatric settings, these techniques have not been widely adopted by practitioners in the field (Liberman et af., Bellack, 1986;Burdett and Milne, 1985;Moss, 1983). In a survey of 152 Veterans Administration Medical Centers, for example, only 20 reported having a behavioral training unit of any kind (Boudewyns et al, 1986).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Therapeutic approaches that are behavioral in orientation have been demonstrated to be cost effective for schizophrenics and other severely disturbed psychiatric populations, in both inpatient (Paul and Lentz, 1977) and outpatient (Liberman, et al, 1987) settings. Paul and Lentz (1977), for example, concluded that a behavioral token economy is the treatment of choice for chronic psychiatric inpatients when compared to active 'milieu' treatment programs or the medication/custodial care routine commonly provided to these patients.Despite demonstrations of the utility and cost effectiveness of behavioral programming in psychiatric settings, these techniques have not been widely adopted by practitioners in the field (Liberman et af., Bellack, 1986;Burdett and Milne, 1985;Moss, 1983). In a survey of 152 Veterans Administration Medical Centers, for example, only 20 reported having a behavioral training unit of any kind (Boudewyns et al, 1986).…”
mentioning
confidence: 99%
“…Several observational studies have noted that nursing and aide staff in public psychiatric hospitals are typically poor behavioral managers (Burdett and Milne, 1985;Niemeier, 1983;Gelfand et al, 1967) and most behavioral interventions require considerable staff effort at the lowest levels of the nursing hierarchy. These personnel are often not inclined to treat patients, but, rather, to keep them from acting out and being a problem (Gardner and Cole, 1987;Boudewyns et al, 1986).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a small, older, exploratory study 121 of the opinions of staff of inpatient rehabilitation wards, the factor that most influenced staff use of behaviour therapy was attendance at the training course (100%), followed by nursing officer and peer support (91%). Marlowe et al's 116 case report compared the experiences of two mental health inpatient units in separate hospitals in Florida, USA, that underwent a staff training programme to implement psychosocial rehabilitation.…”
Section: Unitmentioning
confidence: 99%